Impact of the 2015 Health Information Technology Certification Edition on Interoperability among Hospitals. (28th June 2021) - Pylypchuk, Yuriy; Barker, Wesley; Encinosa, William; Searcy, Talisha
Abstract: Objective: Most nonfederal acute care hospitals use electronic health records (EHRs) certified by the Office of the National Coordinator for Health Information Technology. In 2015, the Office of the National Coordinator for Health Information Technology finalized the 2015 Health IT Certification Edition and adoption by hospitals began in 2016. We examine the impact of the 2015 Edition on rates of interoperable exchange among nonfederal acute hospitals. Materials and Methods: The study applies a standard difference-in-differences design and a recently developed fixed effects estimator that relaxes the assumption of treatment effects being constant across groups and time. In the analysis, we identify separate effects of the 2015 Edition for hospitals that switched EHR developers and forecast hospitals' interoperability over 2015 Edition adoption rates. Results: The adoption of the 2015 Edition increased hospitals' rates of interoperable exchange and especially benefited hospitals that switched EHR developers in the post-implementation period. Forecasting results indicate that if all hospitals adopted the 2015 Edition, 53% to 61% of hospitals would engage in interoperable health information exchange compared with the current rate of 46%. Discussion: Hospitals' levels of interoperability have been rising over the last few years. Adoption of newer technology improved hospitals' interoperability and accounts for up to 12% of the rise in interoperability. Conclusions: Certified technology is one mechanism to ensure providers use recent and safe technologies for interoperable exchange. Adoption of certified EHRs improves the nation's interoperable exchange; however, it has a clear limited effect. Other mechanisms are necessary for achieving comprehensive interoperable exchange.